2021
DOI: 10.3390/v13112329
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Neutralizing Antibody Responses Following Natural SARS-CoV-2 Infection and Correlation with Commercial Serologic Tests. A Reappraisal and Indirect Comparison with Vaccinated Subjects

Abstract: Neutralising antibodies (NAbs) represent the real source of protection against SARS-CoV-2 infections by preventing the virus from entering target cells. The gold standard in the detection of these antibodies is the plaque reduction neutralization test (PRNT). As these experiments must be done in a very secure environment, other techniques based on pseudoviruses: pseudovirus neutralization test (pVNT) or surrogate virus neutralization test (sVNT) have been developed. Binding assays, on the other hand, measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…This suggests that the antibody response in previously uninfected individuals vaccinated with CoronaVac was significantly lower compared to individuals who have recovered from SARS-CoV-2 infection. 2 , 3 , 41 As shown, more severe individuals had higher antibody titres, which other studies have been associated with increased replication and disease burden. 24 Although lower titres are seen in Coronavac vaccinated individuals, as compared to natural infected individuals, this data indicates that immunization by this vaccine affords protection from COVID-19, as shown in recent vaccine effectiveness studies in Chile.…”
Section: Discussionmentioning
confidence: 60%
“…This suggests that the antibody response in previously uninfected individuals vaccinated with CoronaVac was significantly lower compared to individuals who have recovered from SARS-CoV-2 infection. 2 , 3 , 41 As shown, more severe individuals had higher antibody titres, which other studies have been associated with increased replication and disease burden. 24 Although lower titres are seen in Coronavac vaccinated individuals, as compared to natural infected individuals, this data indicates that immunization by this vaccine affords protection from COVID-19, as shown in recent vaccine effectiveness studies in Chile.…”
Section: Discussionmentioning
confidence: 60%
“…Most of the previous studies used the cPASS assay from GeneSript,showing the correlation of competitive immunoassay to live VNT, with good sensitivity and specificity compared to VNT ( 5 , 6 , 9 , 14 , 15 , 19 , 20 , 22 , 23 ). Only a few studies reported results with the TECO ( 15 , 20 ) or YHLO assays ( 7 , 8 , 21 ). Of note the study of Chan et al ( 21 ) found a diagnostic cutoff, with the YHLO assay, of 27,7 AU/ml, which is closed from ours of 30 AU/ml.…”
Section: Discussionmentioning
confidence: 99%
“…These competitive immunoassays, which can be conducted using qualitative immunochromatographic cassettes or quantitative automated or manual enzyme-linked immunosorbent assay (ELISA) platforms, allow rapid and easy processing of large numbers of samples in conventional serological laboratories. However, the performance of these newly developed commercial sVNT assays by comparison to classical serological assays detecting anti-RBD IgG and/or to the reference plaque reduction neutralization test 50% (PRNT 50 ) performed with live virus has been poorly evaluated up to now ( 6 , 7 , 8 , 9 ). Moreover, previous studies have evaluated the specificity using seronegative and/or prepandemic serum which do not inform if commercial sVNT can differentiate serum with or without neutralizing antibody in seropositive samples.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that most patients with COVID-19 at 6 months post-symptom onset were still positive for neutralizing antibodies (N = 44/52, 84.6%). 15 …”
Section: Discussionmentioning
confidence: 99%